Improvement of the metabolic syndrome and of non-alcoholic liver steatosis upon treatment of hypogonadal elderly men with parenteral testosterone undecanoate - Haider A. (2014)
This is a study of a cohort of 117 men aged between 3469 years, with plasma testosterone levels between 5.912.1nmol/L (N>14.0nmol/L) who were treated with administration of testosterone undecanoate for 1 year as the sole intervention. There was a remarkable improvement of body weight, BMI and waist size along with an improvement of lipid profiles. Liver fat is highly significantly and linearly correlated with all components of the metabolic syndrome. Hepatic inflammation secondary to liver steatosis is a potential contributor to the low-grade inflammation associated with the metabolic syndrome. Elevations of liver enzymes are associated with higher CRP concentrations. Levels of ALT (GPT) AST (GOT) and CRP had decreased significantly after one year of testosterone treatment. At baseline 74/117 met the criteria of the metabolic syndrome as defined by the NCEP and after one year of testosterone treatment this number had declined to 42/117. © J. A. Barth Verlag in Georg Thieme Verlag KG Stuttgart - New York.